Teacher Attitude, Experience, and Background Knowledge Effect on the Use of Inquiry Method of Teaching - Journal, IMR (International Multidisciplinary Research Journal, 2014)
Relatively recent research conducted in the area of science teaching, such as that done by Cole & Beuhner-Brent in 1991, has indicated that current elementary school science instruction is not producing the kind of science literacy desired in relation to the world’s clearly greater future scientific needs. In response, professional science organizations such as the National Science Teachers Association (NSTA) are promoting the use of more activity-driven, inquiry-based instruction in the teaching of science, particularly in the elementary schools (Mastropieri & Scruggs, 1994). Inquiry-based instruction is instruction using hands-on activities that allow children to explore scientific concepts, as well as instruction in which the focus is on using process skills to gain deeper understandings of the connections in science. Studies have shown that an inquiry based, hands-on approach is the best way to teach science in a world where facts change frequently and the difficulty of the issues faced will only increase with time. In response to this need, many region school compounds in Ethiopia have adopted new science series in which the focus is on active learning type of instruction. Yet still, science literacy has been slow to show improvement in young children. This research was conducted to see how much of a role teacher’s attitudes towards science itself, and science instruction in particular, plays in deciding to use an inquiry approach to teaching science. Surveys concerning science background, science training and instruction, and teacher attitude towards science were sent to Debre Markos town teachers currently in elementary classrooms teaching science. Responses were compiled and analyzed, and the results were actually surprising.